Celebrating Diversity - Gaskill, Rex. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
Communication teachers and forensics coaches open up students to new ideas, to new experiences, and to new cultures best when they encourage students to explore new ideas and challenge old ones. Learning has taken place when a student comes to really understand a new concept whether through the research necessary to develop, test, and prove the assertions in a public speech, or through a full and thorough reading and understanding of the ideas of an author whose work she is going to present in an interpretation event. Students should be told about the diversity of the "audiences" they will face as speakers and interpreters, as well as the fact that not all judges will be able to put their prejudices aside and evaluate a performance on its merits. A large team which included a first-rate group of interpreters turned David Mamet's "Sexual Perversity in Chicago" into a Reader's Theater script and performed it at tournaments. They either placed first in their round or last (some judges were openly offended by the material and did not judge the performance on its merits). Students should be taught in advance about diversity as they will find it in topic choice, selection of literature, and variety of types of contestants. (RS)
ERIC Note: Paper presented at the Annual Meeting of the National Communication Association (84th, New York, NY, November 21-24, 1998).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cultural Pluralism; Debate; Debate Format; Diversity (Faculty); Diversity (Student); Higher Education; Judges; Public Speaking; Teacher Role; Debate Tournaments; Opinion Papers; Speeches/Meeting Papers